Evaluation of mechanical properties of engineered cementitious composite for exterior beam-column joints under reversed cyclic loading / Shwan Hussain Said - Shwan Hussain, Said (2016)
This thesis describes the experimental program and results of three different stages of a study. The first stage is concerned with the strength, deformation and toughness characteristics of engineered cementitious composite (ECC) slabs cast with three different polymer fibers namely polyvinyl alcohol (PVA) fibers, polypropylene (PP) fibers and polyethylene (PE) fibers. Results showed significant increase in flexural strength, ductility and toughness for both PVA and PE slabs by increasing the reinforcing index, with unpromising results for PP slabs. The second stage of the project involved testing ECC I-shaped samples under direct tension using two different polymer fibers such as PVA and PE fibers to evaluate the direct tensile stress-strain relationship of ECC. Results showed that the cut-off point for ECC-PVA direct tension I-shaped samples occurred at reinforcing index equals to 527 while the cut-off point for ECC PE samples is apparent at the reinforcing index of 474. The third stage includes casting and testing of fourteen full scale RC exterior beam-column joints to evaluate their performance under cyclic loading. The ECC beam-column joint showed significant improvement in the ultimate shear and moment capacities, as well as in the ductility and damage tolerance compared to the normal concrete (NC) joint. In addition, the ECC-PE beam-column joint showed an increase in the ultimate shear and moment capacities with better ductility and damage tolerance compared to ECC-PVA beam-column joint. Moreover, the usage of higher reinforcing index of fibers in ECC beam-column joint improved the ultimate shear and moment capacities with better ductility and crack propagation. Installation of one lateral steel hoop in the ECC joint zone showed noticeable improvement in the ultimate shear and moment capacities as well as in ductility and damage tolerance compared to ECC joints without steel hoops.